Influence of repositioning guides' color and usage on precision in tooth color measurement with a clinical spectrophotometer - Tauan Rosa SANTANA; Paula Fernanda Damasceno SILVA; Márcia Luciana Carregosa SANTANA; Clara Lemos Leal Barata de MATTOS; André Luis FARIA- (University of São Paulo, 2024)
Abstract Repositioning guides are commonly employed in clinical studies to ensure consistent tooth color measurements. Yet, their influence on measured color remains uncertain. Objective This study evaluated the impact of repositioning guides' color and usage on tooth color measurement using a clinical spectrophotometer. Methodology In total, 18 volunteers participated in this study, in which the color of their upper left central incisor and upper left canine was measured with or without repositioning guides (control). The guides were made from pink, blue, or translucent silicone, as well as an acetate-based bleaching tray. Tooth color was measured in triplicates using a clinical spectrophotometer based on the CIELAB system. The standard deviations of these readings were used to estimate reproducibility, and color differences (ΔE00) between the measurements with guides and the control were calculated. Results Repositioning guides had a minimal effect on L* values and no effect on b* values. The use of pink silicone increased a* values, whereas blue or translucent silicone reduced them. Irrespective of the evaluated tooth, the lowest ΔE00 values were observed for the translucent silicone and bleaching tray. The usage of guides only affected data variability for the L* color coordinate. Conclusion Using repositioning guides can significantly impact the precision of tooth color measurement with a clinical spectrophotometer.